Burundi : Interim Poverty Reduction Strategy Paper Report. (IMF Staff Country Reports; Country Report ;, 2004)
The Poverty Reduction Strategy Paper (PRSP) has been prepared in a context of major political changes. Interim PRSP has come in the midst of a difficult economic situation, marked by falling output and incomes. The strategy seeks to strengthen the processes of consolidating peace and security; rehabilitating victims of the crisis; and rebuilding and reviving the economy. The PRSP places particular emphasis on monitoring and evaluating poverty reduction activities. Formulation and implementation of an appropriate decentralization policy will contribute to the success of the PRSP process.